Development of propagation technique of indigenous AMF and their inoculation response in citrus - QIANG-SHENG WU; JIA-DONG HE; A K SRIVASTAVA; FEI ZHANG; YING-NING ZOU (The Indian Journal of Agricultural Sciences, 2019)
Arbuscular mycorrhizal fungi (AMF) have multi-pronged utility in citrus performance, while their propagation technique is a gap. In this study, indigenous AMF in rhizosphere of Citrus unshiu grafted on trifoliate orange were isolated from fresh root segments (Φ<2 mm), fresh rhizosphere soil (< 4 mm size), and air-dried rhizosphere soil (< 4 mm size) as AMF-source and propagated with white clover. Subsequently, indigenous AMF inocula were inoculated into potted trifoliate orange to assess the inoculated efficiency. Our results showed that AMF isolated from fresh root segments multiplied by 333.9% significantly higher than those isolated from fresh or air-dried rhizosphere soil. Similar results were obtained with regard to root mycorrhizal colonization (37.16–55.41%) and soil hyphal length (3.88–13.38 cm/g) in trifoliate orange after inoculated with AMF-source from root segments. Mycorrhizal trifoliate orange seedlings carrying AMF inoculum from fresh roots exhibited higher plant growth performance, root morphology, leaf P, K, Mg, Cu and Zn levels, and leaf superoxide dismutase, peroxidase, and catalase activities, compared to non-AMF treatment. Our study, hence, suggested that root segments would be a great choice to propagate indigenous AMF for later inoculating into the rhizosphere of target plants.